Repeated Insulin-Like Growth Factor 1 Treatment in a Patient with Rett Syndrome: A Single Case Study - Pini, Giorgio; Scusa, M. Flora; Benincasa, Alberto; Bottiglioni, Ilaria; Congiu, Laura; Vadhatpour, Cyrus; Romanelli, Anna Maria; Gemo, Ilaria; Puccetti, Chetti; McNamara, Rachel; O’Leary, Seán; Corvin, Aiden; et al. (Frontiers in Pediatrics, 2014)
Rett syndrome (RTT) is a devastating neurodevelopmental disorder that has no cure. Patients show regression of acquired skills, motor and speech impairment, cardio-respiratory distress, microcephaly and stereotyped hand movements. The majority of RTT patients display mutations in the gene that codes for the Methyl-CpG binding protein 2 (MeCP2), which is involved in the development of the central nervous system, especially synaptic and circuit maturation. Thus, agents that promote brain development and synaptic function are good candidates for ameliorating the symptoms of RTT. In particular, Insulin-like growth Factor 1 (IGF1) and its active peptide (1-3)IGF1 cross the Blood Brain Barrier, and therefore are ideal treatments for RTT Indeed, both (1-3)IGF1 and IGF1 treatment significantly ameliorates RTT symptoms in a mouse model of the disease In a previous study we established that IGF1 is safe and well tolerated on Rett patients. In this open label clinical case study, we assess the safety and tolerability of IGF1 administration in two cycles of the treatment. Before and after each cycle we monitored the clinical and blood parameters, autonomic function and social and cognitive abilities, and we found that IGF1 was well tolerated each time and did not induce any side effect, nor it interfered with the other treatments that the patient was undergoing. We noticed a moderate improvement in the cognitive, social and autonomic abilities of the patient after each cycle but the benefits were not retained between the two cycles, consistent with the preclinical observation that treatments for RTT should be administered through life. We find that repeated IGF1 treatment is safe and well tolerated in Rett patients but observed effects are not retained between cycles. These results have applications to other pathologies considering that IGF1 has been shown to be effective in other disorders of the autism spectrum.